Responses of potential double cropping areas expansion and appropriate crop management practices to climate change in northern China - Wu, Xianzhong; Wang, Jinxiang; Wu, Jiujiang (Frontiers in Sustainable Food Systems, 2024)
Global climate change has led to increases in the temperature and decreases in the number of frost days in northern China, facilitating a shift from a single cropping system (SCS, spring maize) to a double cropping system (DCS, winter wheat-summer maize rotation). Therefore, under the current climate conditions, DCS expansion should be evaluated, and new planting schemes should be explored. In this paper, we identified the areas with potential for DCS in northern China considering an annual accumulated temperature of >0℃. The World Food Studies simulation model was used to simulate the yield, irrigation requirement (IR), and net income under various crop management conditions when considering the maximum yield and water use efficiency (WUE) of crops. Our results indicated that the potential DCS area increased by approximately 31.51 × 104 km2 in northern China, with the primary DCS areas being located in the provinces of Gansu, Shaanxi, Shanxi, Hebei, and Liaoning. Regarding variety selection, winter wheat and summer maize varieties with early and mid-early maturation were found to be favored for the potential DCS areas. The sowing dates corresponding to the maximum WUEs of the crops were later than those corresponding to the maximum yields. In the potential DCS areas, under the maximum yield condition, the average unit total yield, IR, and net income increased to 2700 kg ha−1, 305 mm, and 607 USD ha−1, respectively, whereas under the maximum WUE condition, increases of 2862 kg ha−1, 284 mm, and 608 USD ha−1, respectively, were observed. The average unit total yield of the DCS was 15927 and 13793 kg ha−1 under the maximum yield and maximum WUE condition, respectively. Our findings may clarify the effects of climate change on agricultural production patterns and indicate suitable crop management practices.